2014
DOI: 10.1016/j.japb.2014.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and status of avifauna in Todgarh-Raoli Wildlife Sanctuary, Rajasthan, India

Abstract: a b s t r a c tUnderstanding the diversity and structure of bird communities is essential to delineate the importance of regional or local landscapes for avian conservation. Birds are very sensitive to environmental changes and are used as a "bioindicator." The study was carried out to explore the diversity and status of avifauna in the Todgarh-Raoli Wildlife Sanctuary, Rajasthan, India, from January 2013 to December 2013. The line transect method was used to cover most of the study area. A total of 142 specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 14 publications
2
22
0
Order By: Relevance
“…There is approximately 9702 bird species recorded throughout the world (Sibley and Monroe, 1990), out of which Indian subcontinent supports 1313 (over 13%) of them (Grimmett et al 2011). Birds are very sensitive to environmental changes and are used as a "bio-indicator" (Koli, 2014); also, because of their high mobility, birds react very rapidly to changes in their habitats (Morrisson 1986;Fuller et al 1995). But due to some adverse climatic conditions and various anthropogenic activities the global diversity of birds has been decreasing in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…There is approximately 9702 bird species recorded throughout the world (Sibley and Monroe, 1990), out of which Indian subcontinent supports 1313 (over 13%) of them (Grimmett et al 2011). Birds are very sensitive to environmental changes and are used as a "bio-indicator" (Koli, 2014); also, because of their high mobility, birds react very rapidly to changes in their habitats (Morrisson 1986;Fuller et al 1995). But due to some adverse climatic conditions and various anthropogenic activities the global diversity of birds has been decreasing in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Hansson et al, (2010) stated that water quality parameter such as dissolved oxygen, water depth, salinity would affect the presence of macrophytes and aquatic invertebrates in wetlands, hence this might be the major reason why Lesser Whistling Duck avoided lakes that were not rich with this food source. It was also reported that water depth was an important variable affecting the habitat selection in water birds (Koli, 2014;Sulaiman et al, 2018) because it directly determined the accessibility of prey while foraging (McMahon & Moreira, 2014;Jayathilake & Chandrasekara, 2015). Wading birds prefer shallow water because foraging efficiency decreases with increasing water depth.…”
Section: Discussionmentioning
confidence: 99%
“…Population of fruiting and flowering trees within the garden area can attract many frugivorous and insectivorous birds to live thereby. It is well known that birds are friends of human as they destroy lots of harmful insects and mosquitoes from the environment (Koli 2014). Therefore, a conservation and awareness plan should be launched by the government with the participation of local communities and institutions to save the resident as well as migratory birds, and also, to know about the ecological functions and values of avifauna.…”
Section: Discussionmentioning
confidence: 99%